2019
DOI: 10.3892/ijmm.2019.4344
|View full text |Cite
|
Sign up to set email alerts
|

Incremental load training improves renal fibrosis by regulating the TGF‑β1/TAK1/MKK3/p38MAPK signaling pathway and inducing the activation of autophagy in aged mice

Abstract: Recent studies have confirmed that kidney tissue fibrosis is closely linked to the natural aging of organs. One of its major characteristics is the reduction of autophagic activity. However, to date, few studies have assessed whether incremental load training is able to improve the occurrence of renal fibrosis caused by natural aging and the underlying mechanisms. In the present study involving male C57/BL mice, an elderly exercise group (OY group) was subjected to progressive load-increasing rotary-bar traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…TGF-β-activated kinase 1 (TAK1), interacts with TGF-β1 and contributes to the development and progression of organ fibrosis through TGF-β1/TAK1/MKK3/p38MAPK, TGF-β1/TAK1/MKK4/JNK, and TGF-β1/TAK1/ NFκB pathways (Kim and Choi, 2012;Biesemann et al, 2015;Li et al, 2017;Wu et al, 2017;Zhou et al, 2018;Bao et al, 2019). Few studies of TAK1 on necroptosis have been reported, and these mostly report on RIPK1-dependent cell death.…”
Section: Ripk3 and Tgf-β1mentioning
confidence: 99%
“…TGF-β-activated kinase 1 (TAK1), interacts with TGF-β1 and contributes to the development and progression of organ fibrosis through TGF-β1/TAK1/MKK3/p38MAPK, TGF-β1/TAK1/MKK4/JNK, and TGF-β1/TAK1/ NFκB pathways (Kim and Choi, 2012;Biesemann et al, 2015;Li et al, 2017;Wu et al, 2017;Zhou et al, 2018;Bao et al, 2019). Few studies of TAK1 on necroptosis have been reported, and these mostly report on RIPK1-dependent cell death.…”
Section: Ripk3 and Tgf-β1mentioning
confidence: 99%
“…The implementation of a load progression (intensity, volume, and density of the exercise) during the training program is one of the main training principles ( 164 ). A load progression protocol ensures that new adaptations are occurring in the body throughout the weeks of training ( 165 ). Therefore, a failure to implement a load progression protocol might produce misinterpretations of the exercise effects.…”
Section: Resultsmentioning
confidence: 99%
“…The TGFb-TAK1 pathway is a shared molecular pathway regulating TyrK, BRD and p38 MAPK signaling. Growing evidence supports the role of TAK1 as a significant regulator of TGFb signaling through the regulation of the profibrotic response in several systems [43][44][45][83][84][85][86][87]. Very recently, it has been shown that the action of Catalpol (an anti-inflammatory and antioxidant drug from Chinese medicinal herb Rehmannia) on DMD histopathology was due to its binding to TAK1 [88,89].…”
Section: Discussionmentioning
confidence: 97%